Metode Analytic Hierarchy Process Dalam Menentukan Promosi Jabatan - Pujiati, Tri Wahyuni; Sikumbang, Erma Delima; Ariani, Fattya; Ramanda, Kresna; Sukmana, Sulaeman Hadi; Azizah, Qudsiah Nur (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Promotion plays an important role for every employee in the workplace, because promotion can offer changes in social status, authority, responsibility and increase in income to every employee who is given the opportunity. In the process of promotion to the position of the DKI Jakarta Province Population and Civil Registry Service, criteria are needed in making a decision. Promotion decisions require different considerations of many different factors and suggestions must be made objectively, if the wrong decision is taken during the promotion process, it will have a negative impact on employees and the Agency. The Analytic Hierarchy Process (AHP) method is applied to examine the effect of each criterion in determining promotions to obtain accurate results in determining the best and most appropriate criteria. The results showed that the "Employee educational background" criterion was the most important criterion for promotion. The results of processing survey data using the AHP method and the Expert Choice survey are not much different from one another. The AHP (Analytical Hierarchy Process) method can determine promotion selection.